Extra-Taxation and Property Right in the European Union Law - López Espadafor, Carlos María (The Age of Human Rights Journal, 2019)
Indirect taxes are the essence -and the main priority- of tax harmonization in the European Union. The vast majority of EU tax harmonization directives refer to this type of taxation. At the same time, indirect taxes constitute the field in which the principles of tax justice are less defined, either regarding EU Member States, or the institutions of the European Union. This is an issue about which no explicit reference has been found within the EU original or primary law; we don’t find it in the Treaty of the European Union or in the Treaty on the Functioning of the European Union. The materialization of the fundamental rights in the area of community taxation will be of crucial importance for the concretion of these principles, especially in relation to the property right. Thus, within the fiscal harmonization of indirect taxation, the extra-fiscal perspective and, particularly within it, the environmental issues, are of especial relevance. We should bear in mind that excise duties represent an essential field within tax harmonization and within them, taxation of energy and energy products is paramount. These products, due to their highly pollutant nature, have an environmental transcendence that needs to be taken into consideration.